SEMANTIC ASPECT OF ARABIC MORPHOLOGY: IDEAS AND THEORIES/ ÙˆÙ‚ÙØ§Øª Ø¯Ù„Ø§Ù„ÙŠØ© ÙÙŠ Ø§Ù„ØµØ±Ù Ø§Ù„Ø¹Ø±Ø¨ÙŠ Ø£ÙÙƒØ§Ø± Ùˆ Ø±Ø¤Ù‰ - Salaudeen, Abdulwahab ajao (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
This research aims to shed light on a semantic aspect of Arabic morphology; the study shows that Arabic morphologists emphasized formative aspect more than the grammatical element which made Arabic morphology difficult to comprehend, it has gone to the level of generalizing some rules without giving semantic element adequate attention. There is no doubt on the fact that the formative element of Arabic morphology has to go side by side with semantic aspect to simplify and clarify its study. However, this research points out the advantages of applying the theory of Semantic /Analytical Field for identifying the characteristics of each morphological forms. The researcher applies the descriptive and analytical method to give a general view of this morpho- semantic study.Keywords: Semantic; Arabic Morphology; Ideas; Visions